3r+9=-3(8r-3)

Simple and best practice solution for 3r+9=-3(8r-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3r+9=-3(8r-3) equation:


Simplifying
3r + 9 = -3(8r + -3)

Reorder the terms:
9 + 3r = -3(8r + -3)

Reorder the terms:
9 + 3r = -3(-3 + 8r)
9 + 3r = (-3 * -3 + 8r * -3)
9 + 3r = (9 + -24r)

Add '-9' to each side of the equation.
9 + -9 + 3r = 9 + -9 + -24r

Combine like terms: 9 + -9 = 0
0 + 3r = 9 + -9 + -24r
3r = 9 + -9 + -24r

Combine like terms: 9 + -9 = 0
3r = 0 + -24r
3r = -24r

Solving
3r = -24r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '24r' to each side of the equation.
3r + 24r = -24r + 24r

Combine like terms: 3r + 24r = 27r
27r = -24r + 24r

Combine like terms: -24r + 24r = 0
27r = 0

Divide each side by '27'.
r = 0

Simplifying
r = 0

See similar equations:

| 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r | | 5x^2-2x-16=2x^2+6x | | 2cos(2x)-cos(x)=0 | | logx+2(0)16=4 | | 7r^2-19r-14=-3r+1 | | 30x^2-20x-28=5x^2+4 | | X/2=62 | | V/2=62 | | 3x(-7x^4y)= | | 25n^2+4n-1=1-5n^2 | | 1.13=ln(x/1) | | -6(8-8p)-7=-15+8p | | 25n^2+4n-1=1-5n | | 1-6(-8k-2)=109 | | 8y+96=3y-9 | | x=23000-(x(.12))+(x(.05)) | | 2m+5=8 | | a+14=17 | | x=23-(x(.12))+(x(.05)) | | log(x)+log(x^4)=5 | | 92=-(-5x-4)+6x | | 3(3a-4)=-84 | | 7a^2-14a=21 | | -8(7k+1)=216 | | 5x-2x*x=2 | | logx+logx^4=5 |

Equations solver categories